Motor planning poststroke: impairment in vector‐coded reach plans. Issue 12 (10th December 2015) - Rizzo, John‐Ross; Hudson, Todd E.; Abdou, Andrew; Rashbaum, Ira G.; George, Ajax E.; Raghavan, Preeti; Landy, Michael S.
Abstract: Healthy individuals appear to use both vector‐coded reach plans that encode movements in terms of their desired direction and extent, and target‐coded reach plans that encode the desired endpoint position of the effector. We examined whether these vector and target reach‐planning codes are differentially affected after stroke. Participants with stroke and healthy controls made blocks of reaches that were grouped by target location (providing target‐specific practice) and by movement vector (providing vector‐specific practice). Reach accuracy was impaired in the more affected arm after stroke, but not distinguishable for target‐ versus vector‐grouped reaches. Reach velocity and acceleration were not only impaired in both the less and more affected arms poststroke, but also not distinguishable for target‐ versus vector‐grouped reaches. As previously reported in controls, target‐grouped reaches yielded isotropic (circular) error distributions and vector‐grouped reaches yielded error distributions elongated in the direction of the reach. In stroke, the pattern of variability was similar. However, the more affected arm showed less elongated error ellipses for vector‐grouped reaches compared to the less affected arm, particularly in individuals with right‐hemispheric stroke. The results suggest greater impairment to the vector‐coded movement‐planning system after stroke, and have implications for the development of personalized approaches to poststroke rehabilitation: Motor learning may be enhanced by practice that uses the preserved code or, conversely, by retraining the more impaired code to restore function. Abstract : Participants with stroke and normal control participants made a series of center‐out reaches on a tabletop. Here, average reach trajectories show that reaches with the more affected limb in stroke are hypermetric.